PENGGUNAAN TEKNIK DIVERSI DALAM PROSES PERADILAN PIDANA ANAK - Warumboy, Charolin Khristy; Mardian Putra Frans (Lembaga Penelitian dan Pengabdian kepada Masyarakat STIH Awang Long, 2024)
This research aims to annotate the application of diversion in Decision Number 7/Pid/ Sus.Anak/2019/PN Jap. In this decision, the child was sentenced to imprisonment for 4 (four) months, while the Public Prosecutor (JPU) as law enforcer was obliged to carry out diversion.